2018
DOI: 10.4992/jjpsy.89.16333
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among children relocating to temporary housing following the Fukushima nuclear accident

Abstract: Mental health among children relocating to temporary housing following the Fukushima nuclear accidentMasae Miura (Tokyo Kasei University) , Ayaka Miura (Yoyogi Hospital) , and Takahiro Okayasu (Meiji University)This study compared the psychological health of children who moved to temporary housing following the Fukushima nuclear accident with those who stayed in their own houses. The questionnaire was designed to measure stress responses, positive events in daily life, positive affect, and social support. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A 3-year follow-up study of people who were evacuated from Fukushima Prefecture reported that the causes of stressors changed from the damage of the earthquake itself to the circumstances of living in shelters over time (20). A small-scale study showed that 28 children who were evacuated from the affected area of the FDNPP accident and lived in temporary housing in the nonaffected area of the Fukushima Prefecture experienced more frequent bullying than 106 children living in their own houses in Fukushima Prefecture and 321 children living in a nonaffected area in the Saitama Prefecture (21). The authors suggested that changes in friendship and the limitation of playground space may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-year follow-up study of people who were evacuated from Fukushima Prefecture reported that the causes of stressors changed from the damage of the earthquake itself to the circumstances of living in shelters over time (20). A small-scale study showed that 28 children who were evacuated from the affected area of the FDNPP accident and lived in temporary housing in the nonaffected area of the Fukushima Prefecture experienced more frequent bullying than 106 children living in their own houses in Fukushima Prefecture and 321 children living in a nonaffected area in the Saitama Prefecture (21). The authors suggested that changes in friendship and the limitation of playground space may have influenced the results.…”
Section: Discussionmentioning
confidence: 99%
“…21 For non-FHMS studies (n = 46; 60.5%), a large number of the studies used convenience samples and focused on evacuees (living in and out of the Fukushima prefecture), children, and older adults. Other study populations focused on specific populations, such as hospital patients, 15,23,45,47,54,85,86 caregivers, 19,71 students, 16,30,33,42,[48][49][50]62 and workers of various occupations. Specifically, a series of studies were conducted among the NPP workers.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…About two-thirds of the examined papers (n = 51; 64.6%) were written in English whereas 28 (35.4%) were written in Japanese. 15,18,25,26,29,35,[47][48][49][50]51,54,56,62,63,[66][67][68]70,72,77,81,84,86,88,91,92 Most studies (57; 75.0%) had a single-wave, cross-sectional design. A small portion of the studies had multiple waves of cross-sectional design (n = 15; 19.0%) 15,20,23,27,28,34,35,52,55,[58][59][60][61]87,88 ; among them, three studies (3.8%) conducted a trajectory analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations